A confiança como fator de influência da percepção de justiça no ambiente de aprendizagem - Andre de Souza Simil (2016)
This study aimed to analyze the relationship between the trust that stricto sensu graduate students in Accounting place in their teachers and their perceptions of justice in the learning environment. Based platform, the theory of organizational justice was used, especially in its three-dimensional model, designed by Bies and Moag (1986), Bies (1987) and Moorman (1991), which includes the distributive justice, procedural and interactional. The research was classified as explanatory with quantitative approach. The perception of justice, dependent variable, was measured by the instrument Revised Classroom Justice Scale, originally built by Chory-Assad (2002) and later adapted to the reality of stricto sensu graduate in Accounting. The database was formed by 222 students of master's and doctoral programs, distributed in 17 universities in the country. Three multiple regression models were estimated, in order to identify the relationship between the perception of justice on the one hand, and trust and sociodemographic factors on the other. Therefore, there was the use of Stata® software / SE 13. The variable trust was segregated in trust in the faculty and trust in management, measured by instruments built and used by Forsyth, Adams and Hoy (2011), translated and adapted. Questionnaires were administered by Google Forms® platform. In addition, the three-dimensional model of perceived justice has been validated through exploratory and confirmatory factor analysis tools. The main results, the survey showed that confidence in the faculty was statistically significant in predicting the three dimensions of perceived justice. The same happened with the trust in management in relation to distributive justice. 8 of sociodemographic variables analyzed, 5 of them showed statistical significance to predict the dependent variable of this study. Among them, one is linked to the characteristic inherent to the student, while others relate to the specifics of each master's and doctoral program and their learning environments. The estimated models of distributive, procedural and interactional justice were able to correctly predict 32.86%, 47.83% and 62.92% of the students' perceptions of justice. It was found that the intensity and frequency of interaction between teachers and students are decisive in the perception of fairness of these students. The methodology used to construct three-dimensional validation of justice confirmed the validity and amount of dimensions of the model. Model adjustments were made, motivated by the Brazilian culture and the characteristics and dynamics own stricto sensu graduate courses.